Detection of Virulence Genes in Aeromonas hydrophila Isolated from Poultry Meat Using PCR Technique - El-Hawary, Sohaila (Journal of Advanced Veterinary Research, 2022)
The present study was conducted to investigate the presence of Aeromonas species especiallyA. hydrophila and to detect the presence of the aerolysin (aerA) and haemolysin (hly) genes in its isolates derived from a total of 80 poultry meat samples including 20 of each of breasts, drumsticks,thighs and wings. The samples were randomly purchased from some local retail shops in Assiut city, Egypt. Aeromonas spp. were isolated from 48(60%) of the samples analyzed, including 11(55%) of chicken breast, 12 (60%) of chicken drumsticks, 10 (50%) of chicken thigh and 15 (75%) of chicken wing. A total of 48 strains were isolated belonging to six species: A. hydrophila 14 (17.5%), A. caviae 5 (6.25%), A. jandaei 7(8.75%), A. trota 1 (1.25%), A. schubertii 6 (7.5%) and A. allosacharophila 15 (18.75%). All the recovered A. hydrophila organisms were confirmed by PCR assay for the presence of 16S rRNA gene and 9 strains of the tested isolates harboured this gene. Whereas the aerA and hly virulence genes were present in eight and five of A. hydrophila strains out of nine isolates tested, respectively. Strict hygiene measure should be taken to minimize the contamination of poultry meat with Aeromonas spp.